2014
DOI: 10.1080/02699931.2014.890094
|View full text |Cite
|
Sign up to set email alerts
|

The influence of working memory on the anger superiority effect

Abstract: The anger superiority effect shows that an angry face is detected more efficiently than a happy face. However, it is still controversial whether attentional allocation to angry faces is a bottom-up process or not. We investigated whether the anger superiority effect is influenced by top-down control, especially working memory (WM). Participants remembered a color then searched for differently colored facial expressions. Just holding the color information in WM did not modulate the anger superiority effect. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For example, attentional guidance toward VWM-matching information was observed, although this attentional shifting was not observed when the VWM-matching stimulus was always a distractor in a visual-search task (Woodman et al, 2013;Woodman & Luck, 2007). In addition, an increased probability that a target in a visual-search task matched the content of VWM-enhanced attentional guidance from VWM (Carlisle & Woodman, 2011;Kiyonaga, Egner, & Soto, 2012;Moriya, Koster, & De Raedt, 2014a). Future study should manipulate the probability of valid and invalid trials and investigate the effects of strategic control on attentional allocation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, attentional guidance toward VWM-matching information was observed, although this attentional shifting was not observed when the VWM-matching stimulus was always a distractor in a visual-search task (Woodman et al, 2013;Woodman & Luck, 2007). In addition, an increased probability that a target in a visual-search task matched the content of VWM-enhanced attentional guidance from VWM (Carlisle & Woodman, 2011;Kiyonaga, Egner, & Soto, 2012;Moriya, Koster, & De Raedt, 2014a). Future study should manipulate the probability of valid and invalid trials and investigate the effects of strategic control on attentional allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that the content of WM can prioritize relevant emotional information (Grecucci et al, 2010;Moriya et al, 2014), but whether the contents of WM could also exert an influence on emotional information that is not yet consciously processed remains unknown. In the current study, we employed emotional faces in a WM task in conjunction with the b-CFS method and found a robust modulation effect of WM on nonconscious emotion processing (Experiment 1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, faces can be better remembered or maintained in WM when their expressions are angry or fearful rather than happy or neutral ( Jackson, Wu, Linden, & Raymond, 2009;Sessa, Luria, Gotler, Jolicoeur, & Dell'acqua, 2011). Although a plethora of research has demonstrated that emotional salience can exert a powerful modulatory effect on WM ( Jackson, Linden, & Raymond, 2014;Jackson et al, 2009;Sessa et al, 2011), only a few studies have investigated the effect of WM content on emotional processing (Grecucci, Soto, Rumiati, Humphreys, & Rotshtein, 2010;Moriya, Koster, & De Raedt, 2014). It has been found that emotional faces trigger much stronger responses in the fronto-thalamic occipital network when they match an emotional word held in WM than when they do not (Grecucci et al, 2010).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…By using line-drawing objects, Alvarez and Cavanagh (2004) found a high correlation between the reciprocals of VWM capacity and visual search slope. For emotional faces, limited research has investigated attention and memory within the same study (Moriya et al, 2014). Future studies should examine the correlation between emotional bias in visual attention and emotional advantage in VWM.…”
Section: Controlling and Tracking Cognitive Processesmentioning
confidence: 99%